HDAC inhibition prevents white matter injury by modulating microglia/macrophage polarization through the GSK3β/PTEN/Akt axis - Wang, Guohua (Proc Natl Acad Sci U S A, 2015)
Severe traumatic brain injury (TBI) elicits destruction of both gray and white matter, which is exacerbated by secondary proinflammatory responses. Although white matter injury (WMI) is strongly correlated with poor neurological status, the maintenance of white matter integrity is poorly understood, and no current therapies protect both gray and white matter. One candidate approach that may fulfill this role is inhibition of class I/II histone deacetylases (HDACs). Here we demonstrate that the HDAC inhibitor Scriptaid protects white matter up to 35 d after TBI, as shown by reductions in abnormally dephosphorylated neurofilament protein, increases in myelin basic protein, anatomic preservation of myelinated axons, and improved nerve conduction. Furthermore, Scriptaid shifted microglia/macrophage polarization toward the protective M2 phenotype and mitigated inflammation. In primary cocultures of microglia and oligodendrocytes, Scriptaid increased expression of microglial glycogen synthase kinase 3 beta (GSK3β), which phosphorylated and inactivated phosphatase and tensin homologue (PTEN), thereby enhancing phosphatidylinositide 3-kinases (PI3K)/Akt signaling and polarizing microglia toward M2. The increase in GSK3β in microglia and their phenotypic switch to M2 was associated with increased preservation of neighboring oligodendrocytes. These findings are consistent with recent findings that microglial phenotypic switching modulates white matter repair and axonal remyelination and highlight a previously unexplored role for HDAC activity in this process. Furthermore, the functions of GSK3β may be more subtle than previously thought, in that GSK3β can modulate microglial functions via the PTEN/PI3K/Akt signaling pathway and preserve white matter homeostasis. Thus, inhibition of HDACs in microglia is a potential future therapy in TBI and other neurological conditions with white matter destruction.